BURSA EFEK DALAM EKONOMI ISLAM - H Syahrul (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
In the discussion of Islamic thought to reconstruct the conventional financial instruments that are not allowed by Sharai , and circulated in the capital markets , then submit proposals for the Muslim jurist and scientists on the alternative financial instruments in accordance with the new Islamic fiqh . The discussion outlined as follows: 1) The transfer of activities that firms issuing common stock and indulge in the forbidden activity toward longer lawful good , 2) Elimination of the terms relating to the preferred shares as collateral for the return of property and collateral for part of particular benefit to conform with the provisions of law , 3 ) Elimination of bonds that have a fixed interest rate and certain investments and turn them into securities that participate in the profits and losses without any guarantee on its back above the price or profit , 4) the jurist and Muslim scientists have ijtihad in Islamic economics in creating some new securities in accordance with the provisions of Mam . Among them are: Bond mudarabah letter al-muthlaqah al-Islamiya, al-mudaraba Letters Muqayyadah bi masyru ' mu'ayyan , Surat al - mudaraba Muqayyadah bi blunt mu'ayyan , Obiigasi mudaraba which can be converted into shares , Letter of special financing , special investment letter , letters of different deliberation , investment bonds Island.